AB0428 Study on the Efficacy and Safety of Tocilizumab in Patients with Rheumatoid Arthritis in Slovakia: One Year Results of Prospective, Open Label Study Close to Clinical Practice. (10th June 2014) - Rybar, I.; Killinger, Z.; Macejova, Z.; Kmecova, Z.; Zanova, E.; Rovensky, J.
Abstract : Objectives: To analyze the Slovakian experiences in a national multicenter open label non-interventional phase IV study which evaluated tocilizumab (TCZ) in patients with rheumatoid arthritis (RA) and an inadequate response to conventional disease-modifying antirheumatic drugs (DMARDs) or tumor necrosis factor inhibitors (TNFs). Methods: A prospective open label, single arm study with descriptive statistics used to analyze primary endpoint DAS28 and secondary endpoints: physical disability (HAQ) and safety. Adult patients with moderate to severe active RA who are on infusions therapy of TCZ (8mg/kg) every 4 weeks, after inadequate clinical response to a stable dose of DMARDs. Study has been approved by local ethical committees and all patients provided informed consent before enrollment. TCZ can be given with methotrexate (MTX), or as monotherapy in case of intolerance to MTX or when treatment with MTX was inappropriate. Results: In 62 RA patients reached one year retention rate 89%. 7 patients were prematurely withdrawn: one of them because of ineffectiveness, 4 adverse events and 2 other reason (withdrawal of inform consent or loss of control). After one year 63% of enrolled patients were in remission (DAS28<2, 6) and other 19% reached low activity of disease (DAS28≤3, 2). DAS28 index value decreased from baseline rate 6.54±0.78 to 2.99±1.26 (12 week), 2.82±1.21 (24 week), 2.29±1.04 (36 week) and 2.26±1.12 (48 week). After 12 months of TCZ treatment HAQ disability index decreased from average value 1, 63±0, 61 to 1, 21±0, 71, while improvment of the minimal clinically important difference (≥0, 22) was recorded in 63% of patients. There were no new safety signals compared with other clinical studies. Adverse events have been confirmed in 28 patients, in 25 with low and moderate intensity. Serious adverse events occurred in 3 patients (1 arterial thrombosis, 1 acute sciatica with lumbar stenosis, 1 labile blood pressure). No case of death has been reported. Conclusions: TCZ in Slovakian RA patients in open label study demonstrated high degree of one year retention rate (89%) with remission in 63% and low activity of disease in other 19% patient, without new safety signals. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1516